Photoinduced multicomponent regioselective synthesis of 1,4,5-trisubstituted-1,2,3-triazoles: transition metal-, azide- and oxidant-free protocol - Sai Allaka, Bhargava; Basavoju, Srinivas; Rama Krishna, Gamidi (Advanced Synthesis & Catalysis, 2021)
A transition metal- and azide-free approach is explored to synthesize 1,4,5-trisubstituted-1,2,3-triazoles under sunlight. The reaction proceeds via C-N and N-N bond formations. These regioselective 1,2,3-triazoles are obtained from isatin Schiff bases, benzaldehydes and tosylhydrazine in the presence of base. This protocol offers the structurally diverse 1,2,3-triazole derivatives with 75-90% yields.
Keywords: 1; 2; 3-triazoles; 4; 5-trisubstituted-1; azide- and oxidant free protocol; Cycloaddition; milder reaction conditions; molecular diversity; Multicomponent reaction; Regioselectivity; transition metal-

Transition metal- and oxidant-free regioselective synthesis of 3,4,5-trisubstituted pyrazoles by means of [3+2] cycloaddition reactions - Allaka, Bhargava Sai; Basavoju, Srinivas; Gamidi, Rama Krishna (ChemistrySelect, 2022)
A highly efficient regioselective synthesis of 3,4,5-trisubstituted pyrazoles via transition metal- and oxidant-free, three component [3+2] cycloaddition with thiazolidinedione chalcones, benzaldehydes and N-tosylhydrazine is described. The reaction proceeds through C-C and C-N bond formations under mild reaction conditions to produce structurally diverse polysubstituted pyrazoles in moderate to good yields.
Keywords: 3; 4; 5-trisubstituted pyrazoles; Cycloaddition; Multicomponent reaction; Oxidant free; Regioselectivity; Transition metal free

Ionic liquid assisted green synthesis of quinoxaline based bisspirooxindoles: anticancer evaluation and molecular dynamics - Kanchrana, Madhu; Krishna, Gamidi Rama; Dey, Biswajit; Pandey, Nandita; Guru, Santosh Kumar; Sangolkar, Akanksha Ashok; Pawar, Ravinder; Basavoju, Srinivas (CHEMISTRYSELECT, 2024)
Keywords: Cycloaddition; spirooxindoles